Green Budgeting and Budget Efficiency Mediated by Eco-Friendly Technology in Public Institutions - Raden Minda Kusumah; Yoana Nurul Asri; Fotuho Waruwu (Journal of Social Work and Science Education, 2026)
This study aims to analyze the implementation of green budgeting in public institutions and to examine the relationship between green budgeting, budget efficiency, and environmentally friendly technology as a mediating variable. The research involved 52 respondents consisting of operational, IT, and financial planning staff across several public institutions. The method employed was a questionnaire survey and observation, while data analysis was carried out descriptively and inferentially using mediation regression tests. Descriptive analysis results indicate a positive trend across all variables. For green budgeting, 13% of respondents strongly agreed, 73% agreed, 12% were neutral, and 2% disagreed. Regarding budget efficiency, 13% strongly agreed, 73% agreed, 12% were neutral, and 2% disagreed. Similarly, for environmentally friendly technology, 13% strongly agreed, 73% agreed, 12% were neutral, and 2% disagreed. These findings consistently show that the majority of respondents perceive their institutions as supporting environmentally oriented budgeting policies, implementing efficient budget use, and adopting environmentally friendly technologies in operational activities. The inferential test results confirmed that green budgeting has a positive effect on budget efficiency (β = 0.550; p < 0.05). However, after including environmentally friendly technology as a mediating variable, the direct effect of green budgeting on efficiency becomes insignificant (β = 0.180; p > 0.05). This indicates full mediation, where green budgeting enhances budget efficiency through the adoption of environmentally friendly technologies. These findings highlight that green budgeting policies in public institutions can foster efficiency, particularly through document digitization, the use of energy-saving equipment, and the implementation of paperless office policies.